Arteries and anatomic-surgical segments of the adrenal glands in fetuses of buffaloes (Bubalus bubalis) - Curado, Maria Cecília Fleury; Miglino, Maria Angélica; Souza, Wilson Machado de; Didio, Liberato João Afonso (Brazilian Journal of Veterinary Research and Animal Science, 1997)
The arteries and the anatomico-surgical segments of the adrenal glands of 30 fetuses of buffaloes were studied after arterial injection with colored latex-Neoprene and dissection. The right gland, in our cases, appeared to be supplied by 9, and the left by 8 branches, from different sources and showing different arrangements. The anatomicosurgical segments varied in number,from 5 to 11, the average being three on the right (60,0%), and 3 or 4 on the left (63,3%) .